Double-finger-gate controlled spin-resolved resonant quantum transport in the presence of a Rashba–Zeeman gap. (5th February 2015) - Tang, Chi-Shung; Tseng, Shu-Ting; Gudmundsson, Vidar; Cheng, Shun-Jen
Abstract: We investigate double finger gate (DFG) controlled spin-resolved resonant transport properties in an n-type quantum channel with a Rashba–Zeeman (RZ) subband energy gap. By appropriately tuning the DFG in the strong Rashba coupling regime, resonant state structures in conductance can be found that are sensitive to the length of the DFG system. Furthermore, a hole-like bound state feature below the RZ gap and an electron-like quasi-bound state feature at the threshold of the upper spin branch can be found that is insensitive to the length of the DFG system.